A distributed IP address assignment scheme in ad hoc networks. (14th January 2008) - Sheu, Jang-Ping; Tu, Shin-Chih; Chan, Li-Hsiang
In this paper, we present a scheme to assign IP address to each newly-joined node. First, some nodes are selected as coordinators. Then a new node will use the exchanged hello messages to find the closest coordinator and obtain a new IP address from that coordinator. In order to efficiently maintain the IP-address pools, the distributed coordinators are organised in a tree topology by exchanging hello messages. Simulation results show that our proposed scheme has a low latency for obtaining a new IP address and that it can efficiently maintain consistent IP-address pools.